Feasibility and Acceptability of a Self-Report Activity Diary in Families of Children With and Without Special Needs. Issue 4 (2nd October 2019) - Forseth, Bethany; Papanek, Paula E.; Bandini, Linda; Schoeller, Dale; Moosreiner, Andrea; Sawin, Kathleen J.; Zvara, Kimberley; Fendrich, Michael; Polfuss, Michele
ABSTRACT: This study was conducted to examine the feasibility and acceptability of a self-report activity diary completed by parents and older children to assess the child's daily activity in children with and without special needs. The study included 36 child/parent dyads stratified by child age and diagnosis. Parents (n = 36) and children ≥13 years (n = 12) were asked to report on the child's daily activity using an activity diary. Feasibility was determined based on successfully returned diaries and acceptability via post-study interview. Activity diaries were submitted by 94% of the parents and 100% of the children, with 83% and 80%, respectively, successfully completed. Comments provided post-study regarding the diaries were primarily on the format and were generally negative. The activity diary was feasible to use, but not well accepted within our sample of children with and without special needs or their parents. Further research is needed to create valid physical activity assessment measures that are population specific for individuals with special needs.